2017
DOI: 10.3390/ijerph14030251
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Chronic Diseases and Multimorbidity in a Primary Care Context of Central Argentina: A Web-Based Interactive and Cross-Sectional Study

Abstract: Global health agencies estimate an increase of chronic diseases in South America. Nevertheless, few studies have investigated chronic diseases and their risk factors in the perspective of multimorbidity. This research aimed to identify these aspects in a primary health care setting of central Argentina. The Pan America version of the STEP wise approach surveillance (STEPS) instrument of the World Health Organization was applied to 1044 participants, 365 men and 679 women, with a mean age of 43 years. High prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 74 publications
(100 reference statements)
6
48
0
4
Order By: Relevance
“…HTN was the most prevalent disease among men and women, regardless of age [8,31,36,37]. The prevalence of HTN and dyslipidemias were the highest in men and women under 65.…”
Section: Relationship With Existing Literaturementioning
confidence: 97%
See 2 more Smart Citations
“…HTN was the most prevalent disease among men and women, regardless of age [8,31,36,37]. The prevalence of HTN and dyslipidemias were the highest in men and women under 65.…”
Section: Relationship With Existing Literaturementioning
confidence: 97%
“…The results of the association rule analysis provide probabilities of pair-wise combinations of morbidities that occur more frequently than expected by random chance [26]. These results may help healthcare providers in recognizing the risk of subsequent diseases while assessing patients without multimorbidity, and in determining intervention and prevention strategies to prevent occurrence of multimorbidity [37]. For example, the results revealed that the pair of diseases with the highest lift, among both men and women, was DM dyslipidemias.…”
Section: Relationship With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported a sex disparity in the prevalence of multimorbidity, with reports from both HICs and LMICs indicating that multimorbidity is more common in women (see Annex 6). 296,297,298,299,300,301,302,303,304,304,305 However, other studies have not observed such differences (also see Annex 6). 306,307,308,309,310 A systematic review of observational studies performed across Europe, the United States, Canada, and Australia reported that multimorbidity prevalence was significantly higher in women in nine studies, but not in another five.…”
Section: Sexmentioning
confidence: 98%
“…Olivares DE, et al (2017). 633 Cross-sectional analysis of baseline data from a health promotion activity programme developed in a socioeconomically disadvantaged area of central Argentina.…”
Section: Study Population and Setting Multimorbidity Definition Aimsmentioning
confidence: 99%